PROGRAM PENGEMBANGAN KEWIRAUSAHAAN MAHASISWA DAN ALUMNI STMIK KAPUTAMA SECARA ONLINE - Ambarita, Indah; Sihombing, Anton; Buaton, Relita (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2018)
Developed countries in general are the countries that have many entrepreneurs because they can create jobs, reduce unemployment and contribute to state revenue. Technological development has a correlation with lifestyle and behavior. The internet is not only used to access information, but is also used for business facilities and buying and selling transactions. Currently conventional marketing is less than optimal. Therefore, entrepreneurs are directed to utilize information technology or commonly called commercial electronics as a medium of promotion and sale. This has become a huge opportunity for students or alumni of computer science such as STMIK Kaputama students and alumni. Small and Medium Enterprises (SMEs) in many regions are successful in terms of production, but they have problems in terms of marketing and sales. This has the potential to be developed by young, new and creative entrepreneurs by involving students and alumni to synergize with SMEs and entrepreneurs to deal with online marketing and sales issues, so that market and sales are increasing. The solution provided is making entrepreneurship training by providing various life skills and adding insight into entrepreneurship, e-commerce training, graphic design training, mentoring and supervision. Thus, students and alumni are generally interested in entrepreneurship, and are more easily trained to become entrepreneurs because in lectures they already have basic knowledge of entrepreneurship and computer science and help the government to create jobs and reduce unemployment.Keywords: Increasing entrepreneurship, increasing sales of SMEs, online entrepreneurship, e-commerce